1998
DOI: 10.1096/fasebj.12.13.1409
|View full text |Cite
|
Sign up to set email alerts
|

Putative susceptibility markers of coronary artery disease: association between VDR genotype, smoking, and aromatic DNA adduct levels in human right atrial tissue

Abstract: Cancer and cardiovascular diseases share risk factors such as smoking, and the onset of both diseases have been suggested to have a common mechanistic basis. The binding of carcinogens to DNA (carcinogen‐DNA adducts), genetic polymorphisms in carcinogen‐detoxifying enzymes glutathione S‐transferases (GSTs), and genetic polymorphisms in the vitamin D receptor (VDR) are among the candidates for modifiers of cancer risk. We determined whether these biomarkers could be related to individual characteristics of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(72 citation statements)
references
References 53 publications
3
66
1
2
Order By: Relevance
“…It seems that vitamin D functions may play a role in the pathogenesis of hypertension as a negative endocrine regulator of renin biosynthesis [27] and have a favourable effect on cardiovascular disease [28,29]. Other researchers have also reported an association between the bb genotype and severe coronary stenosis [30].…”
Section: Discussionmentioning
confidence: 98%
“…It seems that vitamin D functions may play a role in the pathogenesis of hypertension as a negative endocrine regulator of renin biosynthesis [27] and have a favourable effect on cardiovascular disease [28,29]. Other researchers have also reported an association between the bb genotype and severe coronary stenosis [30].…”
Section: Discussionmentioning
confidence: 98%
“…These included variations in circulating levels of 1,25-(OH) 2 D 3 (10), variations in bone mineral density (11), modulation of intrauterine and early postnatal growth (12), severity of coronary artery disease (13), and also susceptibility to type 1 diabetes (14,15) and variations in insulin secretion in response to glucose (16). Indeed, an association of alleles of single nucleotide polymorphisms (SNPs) in the VDR gene with increased or decreased insulin secretion in response to an oral glucose tolerance test was observed in a cohort of Bangladeshi Asians (16) recruited from a population considered at risk for type 2 diabetes (5).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of DNA-adducts in abdominal aorta fragments taken at surgery from patients suffering of severe atherosclerotic lesions. 15,[33][34][35] DNA-adduct levels were significantly correlated with the occurrence of atherogenic risk factors and the severity of coronary artery disease. 15,33 The presence of chromosomal alterations and oxidative DNA damage has been recently demonstrated by our group by using the micronucleus test (MN) and the comet assay which are sensitive biomarkers of genetic damage.…”
Section: Genetic Instability Relevant To Atherosclerosismentioning
confidence: 99%
“…15,[33][34][35] DNA-adduct levels were significantly correlated with the occurrence of atherogenic risk factors and the severity of coronary artery disease. 15,33 The presence of chromosomal alterations and oxidative DNA damage has been recently demonstrated by our group by using the micronucleus test (MN) and the comet assay which are sensitive biomarkers of genetic damage. [36][37][38][39] Our data indicated an overall elevation of chromosomal alteration and oxidative DNA damage in peripheral blood lymphocytes of patients with coronary artery disease.…”
Section: Genetic Instability Relevant To Atherosclerosismentioning
confidence: 99%